Evaluation of Knee Stabilization Strategies In Adolescent Males and Females with and Without an ACL Injury During the Lunge and Drop Vertical Jump - Geck, Joanna (Université d'Ottawa / University of Ottawa, 2022)
Purpose: Adolescents have significantly higher rates of diagnosed anterior cruciate ligament (ACL) injuries compared to adult cohorts. Approximately two-thirds of ACL injuries are non-contact scenarios that occur while performing “high-risk” maneuvers. Less than 50% of adolescents are able to return-to-activity, with females specifically having a lower activity level post-injury (Hewett, Di Stasi, & Myer, 2013; Schmale, Kweon, Larson, & Bompadre, 2014). Identifying the quantitative demand of a task used to assess return-to-activity will help establish its role in evaluating the knee stabilization strategies based on muscular coactivations and biomechanical outputs. Therefore, the aim of this study was to (1) assess the neuromuscular and biomechanical quantitative outputs of the lunge and drop-vertical jump (DVJ) in healthy adolescent male and females athletes and (2) to examine the muscular coactivation strategies of adolescent male and female athletes with and without an ACL injury. Methods: A total of 68 uninjured adolescent male and female athletes between the ages of 10 to-18 were used to identify the quantitative demand of the lunge and DVJ. Neuromuscular and biomechanical quantitative outputs included mean peak knee flexion (PKF), integrated knee excursion (iKEXC) in the sagittal and frontal planes, integrated knee joint power (iJP), and integrated electromyography (EMG) were used to assess the within (task) and between (sex) interactions. An additional 17 male and 37 female adolescents with an ACL injury were included to assess the impact of an ACL injury on the knee stabilization strategies (coactivations) used to maintain dynamic knee joint stability (frontal plane knee excursion). Ethics was approved by the University of Ottawa Research Ethics Board (uOttawa REB H09/17/10) (CHEO REB 17/74X). Results: Quantitative data for uninjured groups indicated that the lunge produced greater peak knee flexion, knee excursion, and quadriceps activation values than the DVJ. Conversely, the DVJ produced greater joint power, biceps femoris, gastrocnemii, and gluteus medius values. As for knee stabilization strategies, during the DVJ female ACL injured groups produced greater symmetry and higher muscular activations between anterior-posterior and medial-lateral muscular coactivations, which resulted in increased stability compared to uninjured female groups. Males with an ACL injury indicated similar knee stabilization strategies however decreased stability compared to males without an ACL injury. Conclusion: Results of this thesis identified differences in quantitative data between the lunge and DVJ, indicating differing demand requirements for each task. Results of the second study indicate that uninjured females use knee stabilization strategies that do not restrict their degrees of freedom through asymmetrical coactivations, while females with an ACL injury have increased coactivations in both anterior-posterior and medial-lateral muscle groups, resulting in increased dynamic knee joint stability as evidenced by reduced frontal plane knee excursion motion. Males, however, failed to show a difference between groups in dynamic knee stability, suggesting that those with an ACL injury compensated in a way to perform the DVJ efficiently and similarly to the uninjured group, while maintaining dynamic knee joint stability. In a clinical setting, these findings may help in understanding the direction of use of the lunge and DVJ tasks in a rehabilitation setting. As well as provide insight into the differing male and female adolescent knee stabilization strategies used to maintain dynamic knee joint stability during functional tasks.
Keywords: Knee Stability; Neuromuscular Control; Knee Injury; Lunge; Drop-Vertical Jump; Adolescent